Learning strategies framed in inclusive education (Ciencias Económicas, 2024)
Currently, universities play a fundamental role in the training of individuals at a higher level. These institutions are great recipients of a heterogeneous student body. In thiscontext of massiveness and plurality, the main challenge for public universities is to provide quality education by deploying inclusive institutional strategies that guarantee the academic continuity of student trajectories. The present work tries to discuss the learning strategies managed in Mathematics as Language chair of the Faculty of Economic Sciences of the Universidad Nacional del Litoral, based on the principles of Universal Learning Design (DUA) proposed by Torrico, Fernández, Gutiérrez Arenas, López González and Naranjo de Arcos (2017) The methodology used is, in the first instance, qualitative. The most relevant data obtained and analyzed in this research are the teaching team's observable practices and the students' opinions. In a second instance, a quantitative approach is used, through data collection to test hypotheses based on numerical measurement.
Keywords: inclusion-education- participation.